INDIVIDUAL TAX COMPLIANCE IN INDONESIA: EVIDENCE FROM TANAH ABANG MARKET AND BENFORD’S LAW - Dedi Sulistyo Nugroho (Fakultas Ekonomi Universitas IBA, 2022)
This study intends to detect Unplanned Evasion (UPE) among individual taxpayers in the Micro, Small and Medium-Sized Enterprise (MSMEs) sector in Indonesia. UPE refers to manipulation by taxpayers at the time of filing their tax obligations. The focus of this study is the Tanah Abang market, which has vital role in the garment and textile trade in Indonesia, where most of the sellers are MSMEs. This research uses Benford's law and internal data from the Directorate General of Taxes (DGT). The results based on the first digit and first two-digit tests showed that reported income did not follow Benford's law. The second digit tests yielded more mixed and only suggestive evidence of non-conformity with the law. To measure the magnitude of UPE, this study uses a distortion factor model, suggesting a distortion of –11.28%. The study concludes that there is substantial UPE at the aggregate. The study further explores heterogeneity by gender and age, finding that UPE is concentrated among men and older taxpayers. With the results of this research, it has an impact on DGT policy making to focus on counseling and supervising among men and older taxpayers.